PEMIKIRAN IMAM AL-ZARNUJI TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN PENDIDIKAN MODERN - Shilviana, Khusna Farida (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Islamic education is expected to be able to shape students who are required to be able to apply religious spiritual values and ethical, but what has not yet achieved what is targeted. As a solution there needs to be an update in the concept of education. The writing of this paper uses library research methods, namely finding and analyzing various information related to the discussion through books, journals and texts related to the discussion. It was found that the thought of al-Zarnuji's education was relevant to the modern era, namely: 1) Educational objectives, relevant from the existence of conformity with national education goals in the 2003 National Education System Law on educational goals, which between the two emphasized morals. 2) Educators, can be seen from the teacher's personal competence, which is a strong personality ability, noble, wise, and authoritative as well as an example for students. 3) students, it is relevant to be seen from the conformity with Law on National Education number 23 of 2003 Chapter V article 12 that students have an obligation to maintain the norms of education. 4) curriculum, can be seen from the basic foundation of Islamic Education curriculum including the basis of religion, and there is also a psychological basis. 5) Education Method, it can be seen that in the present era the memorization method and the discussion method are still used while still based on needs.